추출용매별 귀리의 항산화 및 암세포 증식 억제 활성 - 함현미(Hyeonmi Ham); 우관식(Koan Sik Woo); 박지영(Ji-Young Park); 이병원(Byongwon Lee); 최용환(Yong-Hwan Choi); 이춘우(Choonwoo Lee); 김욱한(Wook Han Kim); 이준수(Junsoo Lee); 이유영(Yu-Young Lee) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2016)
The objective of this study was to determine the antioxidant and anti-proliferative activities of methanol, ethanol, acetone, and ethyl acetate extracts from oats (Avena sativa L.). Total polyphenol contents of extracts were analyzed by Folin-Ciocalteu assay. The antioxidant activities of extracts were determined by 2,2-azino-bis-(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) and 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activities and reducing power. The anti-proliferative activities of colon (HCT116), lung (NCI-H460), and breast (MCF7) cancer cells were investigated. Among solvents, methanol extract showed the highest amount of total polyphenols, which was 8.2 mg gallic acid equivalents/g residue. High levels of ABTS radical [12.1 mg Trolox equivalent antioxidant capacity (TEAC)/g residue] and DPPH radical (4.4 mg TEAC/g residue) scavenging activity and reducing power ($A_{700}=0.39$) were found in methanol extracts. Moreover, methanol extracts indicated higher anti-proliferative activities against HCT116 (69.5%), NCI-H460 (75.2%), and MCF7 (84.8%) cells compared with other extracts. The results show that methanol was the best solvent for extraction of antioxidant and anti-proliferative compounds from oats. Moreover, notable antioxidant and anti-proliferative activities of oats could have significant health benefits. 본 연구에서는 귀리 추출물에 대한 항산화 활성과 암세포 증식 억제 활성을 측정하고 각 추출용매에 따른 차이를 비교 분석하고자 하였다. 추출물의 항산화 활성은 2,2-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid)(ABTS)와 1,1-diphenyl-2-picrylhydrazyl(DPPH) 라디칼 제거능 및 환원력을 이용하여 측정하였으며, 암세포 증식 억제 활성은 대장암, 폐암 및 유방암 세포주를 이용하여 평가하였다. 총 폴리페놀 함량, ABTS 및 DPPH 라디칼 제거능, 환원력 모두 methanol 추출물이 각각 8.2 mg gallic acid equivalent/g residue, 12.1 mg Trolox equivalent antioxidant capacity(TEAC)/g residue, 4.4 mg TEAC/g residue 및 $A_{700}=0.39$로 가장 높은 활성을 나타내었다. 또한 암세포 증식 억제 활성은 methanol 추출물이 대장암(HCT116), 폐암(NCI-H460) 및 유방암(MCF7) 세포에서 각각 69.5, 75.2 및 84.8%로 높은 증식 억제 활성을 나타내었다. 따라서 추출용매에 따라 귀리의 항산화 및 암세포 증식 억제 활성에 차이가 나타나며, 이는 추출용매의 극성에 따라 추출된 생리활성 물질, 특히 폴리페놀 화합물의 용해도 차이로 생각된다. 본 연구 결과는 점차 관심이 높아지고 있는 천연 항산화제 및 항암제로서 귀리에 관한 생리활성 연구에 있어 기초자료로 활용될 수 있을 것으로 생각되며, 귀리의 소비 촉진에 영향을 끼칠 것으로 생각된다.